2020
DOI: 10.1590/1413-812320202510.2.26802020
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à Síndrome Respiratória Aguda Grave em uma Região Central do Brasil

Abstract: Resumo A Síndrome Respiratória Aguda Grave (SRAG) deve ser notificada e investigada. O objetivo do estudo foi analisar o perfil epidemiológico e fatores associados à internação e óbitos por SRAG notificados em Goiás. Estudo de coorte retrospectiva, com dados das fichas de investigação do Sistema de Informação de Agravos de Notificação Influenza Web. Métodos de análise multivariada foram realizados para verificar a associação entre variáveis de exposição com os desfechos internação em UTI e óbito. Entre 2013 e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
4
0
3
Order By: Relevance
“…The SARS caused by COVID-19 is mainly characterized by severe hypoxemia 3 . As clinical signs of this pathology, patients present flu-like symptoms combined with dyspnea or tachypnea, with a respiratory rate (RR) of ≥30 incursions per minute, and/or hypoxemia verified by peripheral oxygen saturation (SpO 2 ) <92% in room air 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The SARS caused by COVID-19 is mainly characterized by severe hypoxemia 3 . As clinical signs of this pathology, patients present flu-like symptoms combined with dyspnea or tachypnea, with a respiratory rate (RR) of ≥30 incursions per minute, and/or hypoxemia verified by peripheral oxygen saturation (SpO 2 ) <92% in room air 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in central-western Brazil, the notified cases of SARS from 2013 to 2018 had a higher frequency among females, aged over 60 years and of brown ethnicity; in 99% of cases there was hospitalization, 34% of these in the intensive care unit. 12 The presence of at least one risk factor and/or comorbidity among SARS cases was high, especially cardiovascular diseases, diabetes mellitus, chronic kidney disease, and neoplasms. The high prevalence of comorbidities present in the study reflects the national scenario; in Espírito Santo, a study investigating factors related to hospital death from COVID-19 in 2020 was developed, and it was observed that the same chronic diseases mentioned above were linked to the worst prognosis, noting that 71% of smokers died.…”
Section: Discussionmentioning
confidence: 99%
“…Physical capacity assessment in patients hospitalized with COVID-19 diagnose Evaluación de la capacidad física en pacientes hospitalizados por Bianca Setra Kovalski 1 , Letícia Gonçalves Vergel 2 , Fernanda Diório Masi Galhardo 3 , Simone Fernandes Davi Marques 4 , Aline Maria Heidmann 5 , Eduardo Selan Lopes Gonçales 6 RESUMO | A infecção por SARS-CoV-2 pode ocasionar a síndrome respiratória aguda grave (SRAG), levando a hipoxemia. A avaliação da capacidade física pode ser realizada anteriormente à alta hospitalar, através de testes de exercícios submáximos.…”
Section: Avaliação Da Capacidade Física Em Pacientes Hospitalizados C...unclassified